Application of Environmental Protection Principle in Developing Tourism Potentials of Ebonyi State - Otta C. O; Ngoka P. C; Obinwanne C. O; Enemuo B. O (MultiTech Publisher, 2023)
The study assessed the application of environmental protection principles in Ebonyi State's tourism potentials. A field survey was conducted in Ebonyi South and North senatorial districts, with a sample size of 560 respondents. The research found that key tourism players in the state have not fully applied environmental protection principles to ensure the distribution of tourism resources. The study concluded that the environmental protection principle is not fully applied in the development of tourism potentials, and recommended that key players should strive to apply it as a sustainable development principle to create a connection between the environment and tourism.